Implementing Flipped Classroom in History: The reactions of eighth grade students in a Portuguese school (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Despite the difficulties of integrating every student, every teacher and every school in the digital revolution of the 21st century, there are new tendencies in education using digital technology that are trying to change the everyday life in schools. The Flipped Classroom is one of them. This is a blended learning model that reverses the traditional teaching learning model, putting the student in focus, using digital technology (or not) to learn the contents for homework, usually in small videos, and spend the class time in the application of resources, usually in motivating activities. Following this path, this paper is the result of a case study that we performed in the school year of 2015/2016, with about 80 students, with average ages of 13, in the classroom of History. To complete this experience, we planned an inverted History class, pursuing the main ideas of this methodology, using apps installed in the students’ personal mobile phones and asking students to develop some activities during the class and after the end of class time. The outcome of this case study aims to be a contribution to the idea that Flipped Classroom can be an innovative strategy that reinforces the dialogues between Historical Education and the use of ICT, as well as an original and well-succeeded methodology in History teaching.
Keywords: History Education; History Teaching; Flipped Classroom; Mobile Learning; Bring your own device (BYOD); New Information and Communication Technologies (NTIC)